Penerapan Metode TOPSIS sebagai Rekomendasi Pemilihan Wisata (Studi Kasus: Kabupaten Cilacap) - Tri Mega Anggraeni; Gita Fadila Fitriana; Cepi Ramdani (Journal of Applied Informatics and Computing, 2021)
Indonesian people have made vacation activities a primary need so that vacations are not just travelling. Now people are starting to travel longer, farther, and more often. When making tourist visits, domestic tourists are faced with many choices of destinations in the city. Cilacap City is one of the cities with many tourist attractions, in this city requires the selection of tourist objects according to the interests and interests of each tourist. So, it takes a recommendation system for the user to achieve the goal. The user can choose the desired tourist destination more effectively. The application of tourist recommendations in Cilacap City aims to overcome the problems that occur to tourists. This application uses a Decision Support System using the TOPSIS method with the development of the Agile methodology. The result implementingon of the topstopicshod in Cilacap City are the recommendation for Mount Srandil tourism by 78%, Momongan Island by 77%, Soesilo Soedarman Museum by 74%, Karang Bolong Fort by 71% and Widarapayung Beach by 63%. So, the recommended result is Srandil Mountain tourism. This application also tests the function software's functionality Blackbox method with 100% results, where users, namely tourists, can understand the application's functionality.